(untitled) - Vermeulen, Ross

Characterization of atypical class I lanthipeptides from the marine bacterium thalassomonas viridans XOM25ᵀ (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.